1988
DOI: 10.1073/pnas.85.8.2706
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage to DNA: relation to species metabolic rate and life span.

Abstract: Oxidative damage to DNA is caused by reactive by-products of normal metabolism, as well as by radiation. Oxidized DNA bases excised by DNA repair enzymes and excreted in urine were measured in four different species to determine the relation between specific metabolic rate (ml of 02 consumed per gram of body weight per hr) and oxidative DNA damage. An average of 6.04 nmol of thymine glycol per kg/day and 2.58 nmol of thymidine glycol per kg/day were found in mouse urine and 1.12 nmol of thymine glycol per kg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
244
2
4

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(254 citation statements)
references
References 16 publications
4
244
2
4
Order By: Relevance
“…There is a large body of evidence indicating that ROS play a pathogenetic role in carcinogenesis [35]. During the initiation phase of this process, ROS may interact directly with DNA, damaging specific genes that control cell growth and differentiation, among others [36]. They can also increase the activity of carcinogenic xenobiotics by facilitating their activation to reactive compounds [37].…”
Section: Hepatocellular Carcinoma and Free Radicalsmentioning
confidence: 99%
“…There is a large body of evidence indicating that ROS play a pathogenetic role in carcinogenesis [35]. During the initiation phase of this process, ROS may interact directly with DNA, damaging specific genes that control cell growth and differentiation, among others [36]. They can also increase the activity of carcinogenic xenobiotics by facilitating their activation to reactive compounds [37].…”
Section: Hepatocellular Carcinoma and Free Radicalsmentioning
confidence: 99%
“…Oxidative damage to DNA could be a major factor in cancer and aging [7,24,25,28]. Damage is caused by reactive oxygen species, lipid hydroperoxides and their radical and aldehydic degradation products [29,30], and oxidation products of aromatic amino acids and purines.…”
Section: Oxidative Damage To Dna and Its Relationship To Cancer And Amentioning
confidence: 99%
“…Oxygen-dependent DNA damage is also observed with aflatoxin B~ [40] and phorbol esters [41,42]. The formation of thymine glycol and thymidine glycol in vivo has been used as a possible assay for oxidative DNA damage [28,43]. Very recently, the formation of 8-hydroxydeoxyguanosine in DNA by oxygen radicals was reported [44][45][46][47][48][49].…”
Section: Oxidative Damage To Dna and Its Relationship To Cancer And Amentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the accumulated data have revealed that similar genes affect the aging process in different species but that they act in networks that get more complex and redundant when moving up the evolutionary ladder (Kuningas et al 2008). It is well established that the amount of DNA damage per unit time correlates negatively with life span across species (Adelman et al 1988). In addition, the DNA repair capacity correlates with life expectancy in different mammals (Hart and Setlow 1974;Burkle et al 2005).…”
Section: Szilard's Assumptionsmentioning
confidence: 99%